Correlation between Individual Characteristics, Workload, and Noise with Work Fatigue - Nita Desti Rahmawati; Abdul Rohim Tualeka (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Work fatigue decreases preparedness that raises the risk of workplace accidents. Some of the factors that cause work fatigue are workers characteristics, workload and noise. The purpose of this study is to analyze the correlation between those factors and work fatigue among workers of PT Kerta Rajasa Raya in circulator loom unit. Metods: This is a descriptive observational study that uses a cross sectional approach. This study uses total sampling with a total member of 44 workers. The variables in this study are labor characteristics, including age, gender, years of service, education level, nutritional status, and medical history, which are obtained from questionnaire. Physical workload is assessed based on SNI 7269-2007. Mental workload is measured using NASA-TLX questionnaire. Noise is measured using Sound Level Meter. These variables are the independent variable. The dependent variable, on the other hand, is work fatigue, which is measured by reaction timer. Data are analyzed using Spearman correlation coefficient test (Spearman rho). Results: The results show that 27 workers (61.4%) experienced mild work fatigue and one labor (2.3%) experienced moderate work fatigue. Conclusion: The study concludes that mental workload has the strongest correlation with work fatigue (ρ = 0.509), while medical history has the weakest correlation with work fatigue (ρ = 0.034). Keywords: mental workload, noise, reaction timer, work fatigue